Mastering meta‐analysis in Microsoft Excel with MetaXL add‐in: A comprehensive tutorial and guide to meta‐analysis - Ibrahim Elmakaty (14614270) (2024)
Rationale Meta‐analysis, a powerful technique for combining effect estimates from multiple studies, enhances statistical power and precision. However, its adoption can be hindered by challenges in statistical interpretation and the complexity of specialized software. MetaXL, a freely available Microsoft Excel add‐in, aims to mitigate these barriers by providing comprehensive support and facilitating seamless integration of meta‐analytical results into research publications. Aims and Objectives This tutorial illustrates the practical application of MetaXL for synthesizing meta‐analytical evidence, with a focus on common effect sizes and their presentation. Method This paper reintroduce MetaXL's functions and provide concise explanations of common effect sizes employed in meta‐analysis. The tutorial delves into fundamental concepts such as the selection of appropriate effect sizes for pooling and the choice of meta‐analytical models. Eight illustrative examples are presented, incorporating diverse effect sizes and data formats, including scenarios involving incidence rate ratios, weighted and standardized mean differences, hazard ratios, and prevalence. Additionally, key concepts in network meta‐analysis are discussed, along with their implementation in MetaXL. MetaXL provides convenient access to data formatting templates tailored to various data types and effect sizes encountered in included studies. Results and Conclusion This tutorial offers researchers, particularly those with limited resources, detailed explanations and insights into commonly used methodologies for pooling effect sizes. Furthermore, it introduces the new Excel functions that comes with the MetaXL add‐in. Accurate population of this function and adherence to the correct format are essential to ensure error‐free analyzes. Other Information Published in: Journal of Evaluation in Clinical Practice License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/jep.14138